2021
DOI: 10.1097/hjh.0000000000002960
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics, practice patterns, and outcomes of patients with acute severe hypertension visiting the emergency department

Abstract: Objectives: Data regarding acute severe hypertension, a life-threatening condition encountered in the emergency department, are limited. We aimed to identify the characteristics, practice patterns, and outcomes of patients with acute severe hypertension in the emergency department.Methods: This cross-sectional study at a tertiary referral centre included patients aged at least 18 years who were admitted to the emergency department between January 2016 and December 2019 for acute severe hypertension, which was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(51 citation statements)
references
References 30 publications
0
46
0
Order By: Relevance
“…In particular, acute and severe BP elevations due to uncontrolled hypertension are serious problems commonly encountered in patients visiting the emergency department (ED). According to our previous study, patients with acute severe hypertension, which was defined as systolic blood pressure (SBP) ≥ 180 mmHg or diastolic blood pressure (DBP) ≥ 100 mmHg, accounted for 59 out of 1000 ED visits at a single center and showed poor clinical outcomes, with a 1-year mortality rate of 8.8% and a 3-year mortality rate of 13.9% 4 .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, acute and severe BP elevations due to uncontrolled hypertension are serious problems commonly encountered in patients visiting the emergency department (ED). According to our previous study, patients with acute severe hypertension, which was defined as systolic blood pressure (SBP) ≥ 180 mmHg or diastolic blood pressure (DBP) ≥ 100 mmHg, accounted for 59 out of 1000 ED visits at a single center and showed poor clinical outcomes, with a 1-year mortality rate of 8.8% and a 3-year mortality rate of 13.9% 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Our study showed a much higher mortality rate in patients with hypertensive urgency than expected, reflecting the recent real-world practice data. We previously reported that despite a significantly lower long-term mortality in patients without acute HMOD than in patients with acute HMOD, the values were still very high, with 6.8% and 12.1% after 1 year and 3 years, respectively [7]. In addition, the present study showed that 26.8% of patients with hypertensive urgency were hospitalized during the index visit, and the overall ED revisit and readmission rates were higher than expected: 10.6% and 7.2% within 1 month and 17.7% and 9.9% within 3 months, respectively.…”
Section: Discussionmentioning
confidence: 88%
“…Patients with acute trauma or who only needed a medical certificate were excluded; if they visited the ED multiple times, only data from the first visit were included. Patients with hypertensive crisis were further classified based on the presence of acute target organ damage, such as hypertensive encephalopathy, cerebral infarction, intracerebral hemorrhage, retinopathy, acute heart failure, acute coronary syndrome, acute renal failure, and aortic dissection, which was diagnosed based on clinical data and diagnostic tests, such as blood chemistry analysis, eye fundus examination, 12-lead electrocardiography (ECG), chest radiography, echocardiography, computed tomography (CT), and magnetic resonance imaging [7]. Laboratory data included complete blood count, blood biochemical test findings (levels of electrolytes, renal and liver function tests, and blood glucose), routine urinalysis results, and blood levels of C-reactive protein, D-dimer, brain natriuretic peptide, and troponin-I.…”
Section: Study Populationmentioning
confidence: 99%
“…Patients with hypertensive crisis were further divided into hypertensive emergency and hypertensive urgency according to the presence or absence of acute HMOD. Acute HMOD was defined by the presence of one of the following conditions: hypertensive encephalopathy, cerebral infarction, intracerebral haemorrhage, retinopathy, acute heart failure, acute coronary syndrome, acute renal failure and aortic dissection [ 8 ].…”
Section: Methodsmentioning
confidence: 99%
“…Data were collected using the electronic medical records. The detailed study design and definitions of comorbidities in our study have been published previously [ 8 , 9 ]. Briefly, baseline data for enrolled patients were obtained at the index visit of ED, and events during the follow-up periods were obtained until death from any cause or the end of the study (March 2021).…”
Section: Methodsmentioning
confidence: 99%